Bioinspired Nacre‐Like Ceramic with Nickel Inclusions Fabricated by Electroless Plating and Spark Plasma Sintering. Issue 5 (2nd January 2018) - Xu, Zhe; Huang, Jiacheng; Zhang, Cheng; Daryadel, Soheil; Behroozfar, Ali; McWilliams, Brandon; Boesl, Benjamin; Agarwal, Arvind; Minary‐Jolandan, Majid
Abstract : Hybrid composites of layered brittle‐ductile constituents assembled in a brick‐and‐mortar architecture are promising for applications requiring high strength and toughness. Mostly, polymer mortars have been considered as the ductile layer in brick‐and‐mortar composites. However, low stiffness of polymers does not efficiently transfer the shear between hard ceramic bricks. Theoretical models point to metals as a more efficient mortar layer. However, infiltration of metals into ceramic scaffold is non‐trivial, given the low wetting between metals and ceramics. The authors report on an alternative approach to fabricate brick‐and‐mortar ceramic‐metal composites by using electroless plating of nickel (Ni) on alumina micro‐platelets, in which Ni‐coated micro‐platelets are subsequently aligned by a magnetic field, taking advantage of ferromagnetic properties of Ni. The assembled Ni‐coated ceramic scaffold is then sintered using spark plasma sintering (SPS) to locally create Ni mortar layers between ceramic platelets, as well as to sinter the ceramic micro‐platelets. The authors report on materials and mechanical properties of the fabricated composite. The results show that this approach is promising toward development of bioinspired ceramic‐metal composites. Abstract : Bioinspired ceramic‐metal composite is fabricated by electroless‐plating of Nickel (metal) on ceramic (aluminum oxide) microplates. The metal‐coated platelets are subsequently aligned by magnetic field and sintered by spark plasma sintering process. The composite shows desirable crack‐deflection properties.